The Impact of the Syrian Conflict on Lebanese Trade - Calì, Massimiliano; Harake, Wissam; Hassan, Fadi; Struck, Clemens (World Bank, Washington, DC, 2015)
The devastating civil war in Syria is arguably one of the major civil conflicts in recent times. The conflict started with protests in March 2011 and soon after escalated to a violent internal war with no end in sight to this date. The conflict has by the end of 2014 caused well in excess of 150,000 fatalities, and 6 million internally displaced people (UN), and led 3 million refugees to move out of the country (UNHCR). Beyond the human tragedy, the conflict has disrupted the functioning of the economy in many ways. It has destroyed infrastructure, prevented children from going to school, closed factories and deterred investments and trade. The economic effects of the war extend beyond the country’s borders affecting also the neighboring countries. In particular trade is one of the main channels through which the effects of the crisis are transmitted to neighboring countries. For example, the demand for goods and services in Syria is likely to have fallen thus affecting the many exporters to Syria in neighboring countries. Moreover, to the extent that Syria has become harder to cross, the war may have made trade through Syria more difficult. At the same time producers in neighboring countries may have replaced Syrian producers in Syria and in other markets as their productive assets in Syria were destroyed. This report examines the effects of the Syrian war on the Lebanese economy via one of the most important channels through which the economic impact of the war occurs, i.e. the trade channel. In doing so, it partly updates and extends the previous economic assessment of World Bank (2013b) carried out last year. Focusing specifically on trade allows us to examine in more depth the trade effects than that report was able to do. Indeed, we go beyond the effects on aggregate and sectoral imports and exports to also examine the effects on exports at firms’ level, comparing the effects in Lebanon with those in other neighboring countries, including Jordan, Turkey and Iraq.